2021
DOI: 10.1108/ijlma-07-2021-0183
|View full text |Cite
|
Sign up to set email alerts
|

Implications of the UK Equality Law for tele-homeworking: COVID-19 and beyond

Abstract: Purpose The purpose of this study is to examine the practical and legal complexities associated with tele-homeworking in the context of the UK Equality Law. First, the paper provides a background to the recent growth of tele-homeworking as a result of the COVID-19 pandemic, outlining the tenets of the UK Equality Act 2010 and referring to additional legislation pertinent to the ensuing discussion. Second, illustrative case law relevant to the UK Equality Law is put forward to demonstrate the potential challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 47 publications
(51 reference statements)
0
14
0
Order By: Relevance
“…Seven studies (three secondary analysis [46,48,49], three perspective [43,45,50], one primary research [38]) highlighted how the widespread nature of certain pandemic-related accommodations, such as the shift to remote work, the provision of adaptive technologies to facilitate home-working, and the option of more flexible hours lessened some of the stigma that these accommodations had been associated with prior to the pandemic [38,43,45,46,[48][49][50]. Holland [46], for example, observed that some workers with a disability reported a positive experience of working from home during lockdown because their colleagues were also working remotely.…”
Section: Reduced Stigma Around Workplace Accommodationsmentioning
confidence: 99%
See 3 more Smart Citations
“…Seven studies (three secondary analysis [46,48,49], three perspective [43,45,50], one primary research [38]) highlighted how the widespread nature of certain pandemic-related accommodations, such as the shift to remote work, the provision of adaptive technologies to facilitate home-working, and the option of more flexible hours lessened some of the stigma that these accommodations had been associated with prior to the pandemic [38,43,45,46,[48][49][50]. Holland [46], for example, observed that some workers with a disability reported a positive experience of working from home during lockdown because their colleagues were also working remotely.…”
Section: Reduced Stigma Around Workplace Accommodationsmentioning
confidence: 99%
“…Twelve studies (five perspective [45,[50][51][52][53], four secondary analysis [46,48,54,55] and three primary research [38,56,57]) focused on how rapidly workplace accommodations, especially work from home arrangements, were implemented at the onset of the pandemic. Four studies highlighted (drawing from either their own or secondary data) how certain jobs tended to see the swift transition to remote work, particularly management positions and other whitecollar, knowledge-based jobs such as business and finance, education, information technology, and the sciences [38,46,57,58].…”
Section: Rapid Implementation Of Workplace Accommodationsmentioning
confidence: 99%
See 2 more Smart Citations
“…During the pandemic, more than a third of the employees worked from home, with the share of the female being higher than that of men. A recent UK study shows an illustrative case law relevant to the Equality Act, demonstrating that the challenges faced by employees, regardless of gender, are similar when teleworking is applied in the longer term [82].…”
Section: Work-life Balancementioning
confidence: 99%